Three-dimensional simulations of gravitationally confined detonations compared to observations of SN 1991T - Seitenzahl, Ivo R.; Ohlmann, Sebastian T.; Pakmor, Rüdiger; Röpke, Friedrich (Astronomy and astrophysics, 2016)
The gravitationally confined detonation (GCD) model has been proposed as a possible explosion mechanism for Type Ia supernovae in the single-degenerate evolution channel. It starts with ignition of a deflagration in a single off-centre bubble in a near-Chandrasekhar-mass white dwarf. Driven by buoyancy, the deflagration flame rises in a narrow cone towards the surface. For the most part, the main component of the flow of the expanding ashes remains radial, but upon reaching the outer, low-pressure layers of the white dwarf, an additional lateral component develops. This causes the deflagration ashes to converge again at the opposite side, where the compression heats fuel and a detonation may be launched. We first performed five three-dimensional hydrodynamic simulations of the deflagration phase in 1.4 M⊙ carbon/oxygen white dwarfs at intermediate-resolution (2563 computational zones). We confirm that the closer the initial deflagration is ignited to the centre, the slower the buoyant rise and the longer the deflagration ashes takes to break out and close in on the opposite pole to collide. To test the GCD explosion model, we then performed a high-resolution (5123 computational zones) simulation for a model with an ignition spot offset near the upper limit of what is still justifiable, 200 km. This high-resolution simulation met our deliberately optimistic detonation criteria, and we initiated a detonation. The detonation burned through the white dwarf and led to its complete disruption. For this model, we determined detailed nucleosynthetic yields by post-processing 106 tracer particles with a 384 nuclide reaction network, and we present multi-band light curves and time-dependent optical spectra. We find that our synthetic observables show a prominent viewing-angle sensitivity in ultraviolet and blue wavelength bands, which contradicts observed SNe Ia. The strong dependence on the viewing angle is caused by the asymmetric distribution of the deflagration ashes in the outer ejecta layers. Finally, we compared our model to SN 1991T. The overall flux level of the model is slightly too low, and the model predicts pre-maximum light spectral features due to Ca, S, and Si that are too strong. Furthermore, the model chemical abundance stratification qualitatively disagrees with recent abundance tomography results in two key areas: our model lacks low-velocity stable Fe and instead has copious amounts of high-velocity 56Ni and stable Fe. We therefore do not find good agreement of the model with SN 1991T.
Gesehen am 12.05.2020